LABOR MARKET IN WORLDWIDE GREENING ECONOMY: RESTRUCTURING AND DEVELOPMENT PROBLEMS - L. Gatska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Labor market is affected by ecologization processes in economy both nationally and globally. Positive and negative effects of this process are analyzed in this article. We defined 5 main areas where labor market is affected by "greening" processes: 1) еcologization create new workplaces for producing "green" goods; for implementation and support of ecology-friendly technical processes; in traditional business areas, connected to "greens"; 2) іt provide changes of overall employment rate; 3) labor market structure transform due to new ecology tendencies; 4) current workplaces become "greener", especially positions, connected to ecology; 5) it causes widespread social integration. We made a conclusion that the total effect of this process on labor market will depend on many economic and political factors. Number and quality of created workplaces will highly depend on level of demand for such specialists and on elasticity of employment. It will correlate with the number of workplaces, lost in traditional industries. Sum of gross benefits and damages will be equal to number of employees, who "green" their work conditions or will be forced to change their jobs at all.